Invasion by the box tree moth, Cydalima perspectalis (Lepidoptera: Crambidae), in southeastern Europe - Gábor Vétek, Peter Zach, Dinka Matošević, Katalin Tuba, Ferenc Lakatos, Jan Kulfan, György Csóka, Stanislav Gomboc, Sándor Nagy, Milka Glavendekić, Dimitrios N. Avtzis, Maarten de Groot, Levente Szőcs, Irena Papazova-Anakieva, Sterja Nacheski, Snježana Hrnčić, Sanja Radonjić, Veronika Fekete (All-Russian Research Institute of Silviculture and Mechanization of Forestry East Palearctic Regional Section International Organization for the Biological Control of Pests and Animals, 2019)
The box tree moth, Cydalima perspectalis (Lepidoptera: Crambidae), is native to East Asia and was introduced in Europe more than a decade ago. It causes severe damage to box trees (Buxus spp.) in both urban and natural habitats. The occurrence of this invasive pest in southeastern Europe has not been documented in a comprehensive way yet. The main objective of this study was to obtain a detailed picture of the spread and distribution of C. perspectalis in 11 countries by summarising the records of the species from 2010 to the end of 2016. Data collection was primarily based on reports received from citizens. The results, due to the involvement of citizen science, clearly indicate that the pest was much more widely distributed in this part of Europe as early as 2016 than judged from previously published works. Evidence has been obtained that C. perspectalis was present in Albania, Hungary, and Kosovo, at least one year before its first official record in these countries. This study highlights the utilisation of citizen science in the monitoring of invasive alien species
Invasive dendrophilous organisms: challenges and protection operations. Collective monograph.
Keywords: alien species, Cydalima perspectalis, Buxus, distribution, southeastern Europe, citizen science